The Influence of Financial Literacy and Digital Marketing Literacy on the Performance of Fashion Thrifting Businesses in Makassar City - Tadampali, Andi Caezar To; Arisah, Nur (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study is to find out whether digital and financial literacy affects the performance of MSMEs in fashion thrifting companies in Makassar City. This research was conducted on a fashion thrift store in Makassar City. A quantitative research methodology is used in this study. The object of his research is MSMEs thrifting enterprises in Makassar City. The sampling strategy combines purposive sampling techniques with simple random sampling, with the criteria of MSMEs that have utilized recording applications in their operations, are still actively operating in the year of research, and use social media as a means of promotion. Data collection techniques include surveys, interviews, recordings, and observations. 100 MSMEs that have adopted digital applications received questionnaires. The t-test, the F-test, the Multiple Linear Regression Analysis, and the Classical Assumption Test are all used in the data analysis technique. The findings of the study show that although digital literacy has a large impact on the success of MSMEs in fashion thrifting companies in Makassar City, financial literacy does not have a real impact on the performance of the business.